1997
DOI: 10.1001/jama.1997.03550170042030
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Patient Income and Physician Discussion of Health Risk Behaviors

Abstract: Physician counseling of patients regarding health risk behaviors should be greatly improved if the US Preventive Services Task Force recommendations are to be fulfilled. Improvement is especially needed in regard to alcohol consumption, safe sex, and seat belt use. Physicians also need to be more vigilant in properly identifying and counseling low-income patients at risk in regard to diet and exercise and high-income patients who smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 46 publications
2
37
1
1
Order By: Relevance
“…15 In spite of the growing obesity problem, half or more of obese patients in the United States do not report being counseled about weight loss by their physicians. [18][19][20][21][22][23] Reported counseling from a health care professional about weight, diet, or exercise among overweight and obese adults is lower for some racial/ethnic minorities, 23 persons with lower income 24,25 or less education, 20,21,24 younger persons, 23,24 and men 21,23 than their counterparts.…”
mentioning
confidence: 99%
“…15 In spite of the growing obesity problem, half or more of obese patients in the United States do not report being counseled about weight loss by their physicians. [18][19][20][21][22][23] Reported counseling from a health care professional about weight, diet, or exercise among overweight and obese adults is lower for some racial/ethnic minorities, 23 persons with lower income 24,25 or less education, 20,21,24 younger persons, 23,24 and men 21,23 than their counterparts.…”
mentioning
confidence: 99%
“…16 The finding that the topic of physical activity was raised 41% of the time was somewhat higher than previously reported in other studies. 7,20,36 Yet the question of how much counseling is sufficient, and by whom, is an area of active debate. If we consider that the majority of our participants (78%) were not meeting recommended levels of activity and/or were either overweight or obese (75%), then one could argue that the observed rate of counseling was inadequate to achieve national goals.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Although data from underserved populations are lacking, one study showed that low-income patients with whom physical activity was discussed were significantly more likely to attempt behavior change than were high-income patients. 36 Some data suggest that the last 2 As (Assist and Arrange) may be better achieved by collaboration with allied health educators, community programs, or other health care staff resources given the competing demands that primary care clinicians face. 6,15 Because strong empirical data to support this are lacking, especially among underserved populations, studies should address the role of ancillary professionals in the delivery of counseling and the effect on activity outcomes.…”
Section: Assistmentioning
confidence: 99%
“…Taira et al showed that physicians were more likely to discuss diet and exercise with high-income patients than those from a low-income group; however, they were more likely to discuss smoking with low-income patients. 12 A rich international literature highlights that a patient's inclination to participate in medical decision making, notably on cardiovascular disease management, varies by characteristics, such as age and education, but also by sex, coping style, and severity of condition. [13][14][15][16][17][18] This emphasises the health disparities, notably concerning the management of cardiovascular risk factors in the context of primary care.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%